Nurses' job embeddedness and turnover intention: A systematic review and meta-analysis - Xin Wang; Ming Liu; Angela Y.M. Leung; Xiaoyan Jin; Hongxia Dai; Shaomei Shang (Elsevier, 2024)
Objective: This study aimed to review the relationship between job embeddedness and turnover intentions among nurses and explore the effects of the Job Embeddedness Scale, number of years in the career, education, and marital status on this relationship. Methods: The review was conducted by searching the China Knowledge Resource Integrated Database (CNKI), Weipu Database (CQVIP), China Biology Medicine (CBM), Wanfang Database, PubMed, Web of Science, Embase, CINAHL, and APA-PsycNet for articles on nurses' job embeddedness and turnover from intention up to March 2024. The research quality was evaluated using the Agency for Healthcare Research and Quality (AHRQ) assessment criteria. The review protocol has been registered on PROSPERO [CRD42023483947]. Results: The results of this review included 47 studies consisting of 15,742 nurses from seven countries worldwide. A moderate negative correlation was found between job embeddedness and turnover intention (r = -0.487). Furthermore, on-the-job embeddedness (r = -0.527) was more negatively associated with turnover intention than off-the-job embeddedness (r = -0.234). The highest negative correlation was found between sacrifice and turnover intention (r = -0.460), while the lowest was for the link (r = -0.185). Furthermore, the relationship between job embeddedness and its dimensions with turnover intention was affected by different job embeddedness scales, number of years in the career, education, and marital status (P < 0.05). Conclusion: This systematic review and meta-analysis analyzed the relationships between nurses' job embeddedness, dimensions, and turnover intention. Meanwhile, subgroup analysis and meta-regression explored the factors influencing these relationships. It is an important reference for nurse managers to promote nurse retention.